Analysis of Mispronounced Words Produced by Indonesian Secondary Students - Novita Andini; Annisa Maghfirah; Dea Nirwanda Putri (Indonesian Journal of ELT and Applied Linguistics, 2023)
This study aimed to explore the difficulties faced by Indonesian secondary students in speaking English. This study applied quantitative research design with case study. There were two students chosen based on the categories; one student with moderate level of speaking English, and one student with lower level of speaking English. The data were collected through interview, and the researchers record the students’ answers. Then, all the data taken were deeply analyzed into several points. The data found that the students have difficulties in pronunciation English words. There are several mispronounced words done by the students during the interview. It is implied that Indonesian secondary students need more inputs to speak English with correct pronunciation